Oxygen release from hemoglobin has limited effects on mitochondrial respiration measured from red blood cells Reply to the Comment on "Increased retention of functional mitochondria in mature sickle red blood cells is associated with increased sickling tendency, hemolysis and oxidative stress" - Stier, Antoine; Esperti, Sofia; Nader, Elie; Roussel, Damien; Connes, Philippe (Fondazione Ferrata Storti, 2025)
Not available.